CONTEXTO DE LAS EMPRESAS DE CLASE MUNDIAL. UNA CONTRASTACIÓN ENTRE EMPRESAS DE SERVICIOS TURÍSTICOS Y DE MANUFACTURA SOBRE LA COMUNICACIÓN FORMAL EN CIUDAD JUÁREZ, CHIHUAHUA - Delgado, Jorge Herrera; Cuevas-Contreras, Tomás; Bribiescas-Silva, Francisco (European Scientific Journal, ESJ, 2013)
This essay focuses on Formal Communication (CF) in world class companies as well as tourism-related chains and franchises in Ciudad Juarez, Chihuahua. The approach has been focused on how the communication plays an important role between the employees and the company. The perspective of the manuscript highlights the breadth of the phenomenon in formal relationships between actors and how far the field of manufacturing and touristic services differs from each other. Although CF is built in an organizational environment, it should also be noted if the cultural conditions for their understanding and its benefits are institutional or not.